2021
DOI: 10.1111/tpj.15109
|View full text |Cite
|
Sign up to set email alerts
|

The PalWRKY77 transcription factor negatively regulates salt tolerance and abscisic acid signaling in Populus

Abstract: High salinity, one of the most widespread abiotic stresses, inhibits photosynthesis, reduces vegetation growth, blocks respiration and disrupts metabolism in plants. In order to survive their long-term lifecycle, trees, such as Populus species, recruit the abscisic acid (ABA) signaling pathway to adapt to a saline environment. However, the molecular mechanism behind the ABA-mediated salt stress response in woody plants remains elusive. We have isolated a WRKY transcription factor gene, PalWRKY77, from Populus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 73 publications
1
42
0
Order By: Relevance
“…This assay returned a total of seven proteins; remarkably, the WRKY transcription factor, PalWRKY77, had three hits, which suggested that it is a potential target protein of PalPUB79 (Figure 6a ). In a previous study, PalWRKY77 was found to negatively regulate tolerance to salt stress and the ABA response; more specifically, this protein inhibits the expression of PalNAC002 and PalRD26 transcription factors in poplars (Jiang et al ., 2020 ). To determine the interaction between PalPUB79 and PalWRKY77, we re‐constructed the vector expressing an AD‐PalWRKY77 fusion protein, and then subjected this protein to a point‐by‐point yeast two‐hybrid assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay returned a total of seven proteins; remarkably, the WRKY transcription factor, PalWRKY77, had three hits, which suggested that it is a potential target protein of PalPUB79 (Figure 6a ). In a previous study, PalWRKY77 was found to negatively regulate tolerance to salt stress and the ABA response; more specifically, this protein inhibits the expression of PalNAC002 and PalRD26 transcription factors in poplars (Jiang et al ., 2020 ). To determine the interaction between PalPUB79 and PalWRKY77, we re‐constructed the vector expressing an AD‐PalWRKY77 fusion protein, and then subjected this protein to a point‐by‐point yeast two‐hybrid assay.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis , high ABA levels can relieve AtWRKY40‐mediated repression of the ABA‐responsive genes, i.e., ABI4 and ABI5 , by translocating AtWRKY40 from the nucleus to the chloroplast envelope (Shang et al ., 2010 ). In our previous study on woody poplars, PalWRKY77 negatively regulated responses to salt stress and ABA signalling by directly binding to the W‐boxes of the promoters of PalNAC002 and PalRD26 to inhibit their expression (Jiang et al ., 2020 ). Although enhanced ABA levels have been shown to repress PalWRKY77 transcription, the mechanism through which ABA signalling removes the negative effect of PalWRKY77 in woody poplars remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overexpression of two ABA signaling related NAC genes, PalNAC002 and PalRD26, enhanced salt tolerance in Populus alba var. pyramidalis (Jiang et al 2020). Taken together, these studies suggest that NAC family genes could improve salt tolerance in woody plants by different mechanisms, such as enhancing the ROS scavenging capacity, participating in ABA signaling and adjusting osmotic potential.…”
Section: Salinity Effect On Transcription Factorsmentioning
confidence: 80%
“…Therefore, WRKY might be used as a valid TF to improve or complement the production of plants tolerant to drought and salt stresses. Recently, Jiang et al (2020) isolated and characterized a WRKY gene in Populus alba var. pyramidalis.…”
Section: Salinity Effect On Transcription Factorsmentioning
confidence: 99%
“…Interestingly, W box (TTGACC) was identified in half of the CBL-CIPK genes from honeysuckle. W box is recognized by the family of WRKY transcription factors, which is involved in certain developmental processes and stress response, such as drought stress response in tomato ( Ahammed et al, 2020 ), salt response in Arabidopsis ( Xu et al, 2018 ) and populus ( Jiang et al, 2020 ). In general, the identified cis-acting elements here help in understanding their roles in the developmental and various biotic stress-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%